The Role of Social Capital in the Empowerment of Beef Cattle Farming Groups: A Case Study in North Minahasa Regency, Indonesia - Stanly Oktavianus B. Lombogia; Farha Noma Josefin Dapas; Jum Anggriani; Andreas Sapta Finady (UIN Sunan Gunung Djati, 2025)
This study explores the relationship between social capital and the empowerment of beef cattle farming groups in North Minahasa Regency, Indonesia. The main objective is to examine how elements of social capital—particularly trust, proactive behavior, and shared norms—contribute to empowerment indicators such as accountability, access to information, and organizational capacity. A quantitative cross-sectional research design was employed, using structured questionnaires distributed to 30 randomly selected members of active beef cattle farming groups. The data were analyzed using descriptive statistics and Spearman Rank Correlation to measure relationships between social capital variables and empowerment indicators. Qualitative insights from interviews and observations were used to enrich and contextualize the quantitative findings. Results show that proactive action is strongly correlated with access to information (r = 0.854), trust is strongly linked to accountability (r = 0.837), and social norms are closely associated with group responsibility (r = 0.775). These findings suggest that internal social cohesion enhances governance, information-sharing, and collective performance. However, weaknesses in external networking and overdependence on informal structures may limit adaptability and long-term sustainability. The study proposes a three-part policy model: (1) trust-building mechanisms to enhance group accountability, (2) network enhancement strategies to strengthen external linkages, and (3) norm formalization to support internal governance. This model is tailored to the cultural and institutional context of North Minahasa and offers practical pathways for rural empowerment. This research contributes original insight by empirically linking specific social capital dimensions to empowerment in livestock systems, providing a contextualized framework that integrates socio-cultural dynamics with agricultural policy.